Repetição espaçada e sua influência na memória de longo prazo: um estudo teórico e reflexivo - Nascimento, Leonardo Muniz do (Universidade Federal de São Carlos, 2022)
The Medicine course at the Federal University of São Carlos (UFSCar) is based on Problem-Based Learning. The method´s cornerstones are the absence of classical subjects, content integration, as well as problem solving. As a result, students can develop self-learning skills, integrating knowledge during group discussions, and working as a team. Beginning to apply Active Teaching-Learning Methodologies may bring anguish to students accustomed with traditional teaching methods only, especially for the “learn how to learn” understanding, as well as retaining information. Forgetting accompanies us throughout life and is closely associated with disuse of information. Spaced repetition has been proven to be effective in improving the ability to retain information in the long term. It is based on three learning phenomena: spacing effect, testing effect, and active recall. The objectives of the present study are to provide reflection and theoretical subsidies of the process of studying and “learning to learn” throughout Medicine graduation at UFSCar, focusing on forgetting, and using spaced repetition techniques.
Spaced repetition and its influence on long-term memory: a theoretical and reflective study
Keywords: Aprendizagem Baseada em Problemas; Metodologias ativas; Esquecimento; Memória; Repetição espaçada; Problem Based Learning; Active Methodologies; Forgetting; Memory; Spaced Repetition; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM